2017
DOI: 10.17577/ijertv6is100070
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Data Encryption Algorithms in Cloud Platform

Abstract: -The high growth in the cloud computing has reached the each and every corners of the world. The cloud computing offers the dynamically shared resources namely networks, storage, servers, services and applications, without physically acquiring them. So it saves managing cost and time for organizations. Cloud services providers various services like SaaS, Paas, IaaS, NaaS and etc., over the internet. Cloud Computing moves the application software and databases to the large data centers, where the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study showed the performance of the K-Medoids algorithm is superior to the K-Means algorithm in terms of accuracy with an accuracy of 63,24% (Nurhayati et al, 2019). Study on diabetes data to know the characteristics and track the maximum number of patients suffering from diabetes based on the area calculation algorithm, it was found that K-Medoids is the best algorithm for generating clusters 1015 (Anuradha et al, 2014). The purpose of this study was to find out whether K-Medoids can distinguish COVID-19 patients at various ages level and can help the government to break the chain of transmission of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed the performance of the K-Medoids algorithm is superior to the K-Means algorithm in terms of accuracy with an accuracy of 63,24% (Nurhayati et al, 2019). Study on diabetes data to know the characteristics and track the maximum number of patients suffering from diabetes based on the area calculation algorithm, it was found that K-Medoids is the best algorithm for generating clusters 1015 (Anuradha et al, 2014). The purpose of this study was to find out whether K-Medoids can distinguish COVID-19 patients at various ages level and can help the government to break the chain of transmission of COVID-19.…”
Section: Introductionmentioning
confidence: 99%